Toxicological exposures among the pediatric patients at a tertiary care center in Lebanon: the case for establishing a national poison center. (2nd September 2021) - El Zahran, Tharwat; Mostafa, Hala; Hamade, Hani; Hitti, Eveline; Morgan, Brent W.; Kazzi, Ziad
Abstract: Background: Despite its preventable nature, poisoning remains one of the leading causes of morbidity and mortality in the pediatric population. In Lebanon, this population is poorly studied and there is no poison center to which healthcare providers and the public can refer in case of toxicological exposure, leading to unnecessary Emergency Department (ED) visits. This study describes the pediatric toxicological exposures seen at the largest tertiary care center in Lebanon. It also evaluates the appropriateness of ED visits among confirmed or suspected toxicological exposures in children, in order to assess the role of a national poison center in reducing unnecessary ED visits. Methods: This is a secondary analysis of a database for a telephonic medical toxicology service at the American University of Beirut Medical Center, the largest tertiary care center in Lebanon. Data relating to all pediatric patients aged 0–19 years of age were entered into the database by the medical toxicology team. The cases were independently reviewed by 2 medical toxicologists for the adequacy of referral to the ED and performance of invasive procedures. Results: Two hundred and nine exposures were recorded between 15 April 2015 and 31 December 2019, of which 53.1% were females. Children aged less than 5 years were involved in 67.0% of cases while adolescents aged 13–19 years were involved in 21.1%. The most commonly involved substances were analgesics (14.8%) and cardiovascular drugs (10.0%). The majority had no (59.3%) or minor (26.3%) effects and were treated and discharged home (67.5%). More than a third of ED visits were deemed unnecessary by the toxicologists (Kappa = 0.705), and when including only unintentional cases, around 45% of the ED visits were deemed unnecessary (Kappa = 0.677). Conclusion: Our data show that 37% of all pediatric poisoning ED visits and 45% of ED visits due to unintentional pediatric poisonings were unnecessary. Additionally, more often than not lavage suctions were done unnecessarily. Future research investigating the possibility of preventing unnecessary visits by establishing a national poison center is needed.